Ten years of high-sensitivity cardiac troponin testing in the Netherlands: impact on the diagnosis of myocardial infarction. (25th November 2020) - Kimenai, D.M; Appelman, Y; Den Ruijter, H.M; Mills, N.L; Meex, S.J.R
Abstract: Introduction: High-sensitivity cardiac troponin (hs-cTn) assays have enhanced sensitivity for myocardial injury and may lead to an increase in the diagnosis of myocardial infarction. Few real-world studies have investigated the transition from conventional cardiac troponin (cTn) to hs-cTn. We evaluated the impact of implementing hs-cTn assays and sex-specific thresholds in the Netherlands on the diagnosis of myocardial infarction in women and men. Methods: Twelve Dutch hospitals were included (hs-cTnI assay [sex-specific thresholds], n=4; hs-cTnT assay [uniform threshold], n=8). Data from the health insurance claims of consecutive patients with anginal symptoms were collected before (cTn period) and after (hs-cTn period) implementation from January 2008 to December 2017. The proportion of patients with a diagnosis of myocardial infarction overall, and in men and women separately, and one-year mortality was compared before and after implementation of the hs-cTn assay. Results: Across twelve hospitals, a total number of 77, 464 patients presenting with anginal symptoms were included (cTn period: 35, 409 [36.6% women]; hs-cTn period: 42, 055 [34.6% women]). Following implementation of hs-cTn testing the proportion of patients with anginal symptoms diagnosed with myocardial infarction doubled from 24% (3, 111/12, 970) to 48% (7, 014/14, 560) in women, and from 25% (5, 712/22, 439) to 51% (13, 912/27, 495) in men, with similar increases in sites implementing hs-cTnI and hs-cTnT. The proportion of patients diagnosed with myocardial infarction who were women increased in sites implementing sex-specific thresholds (from 36.4% [1, 435/3, 941] to 37.5% [1, 700/4, 532], absolute change 1.1%), but did not increase in sites using a uniform threshold (from 34.3% [1, 676/4, 882] to 32.4% [5, 314/16, 394], absolute change −1.9%). In patients with a diagnosis of myocardial infarction, one-year mortality was 15.6% (485/3, 111) and 11.6% (814/7, 014) in women, and was 11.8% (673/5, 712) and 9.4% (1, 303/13, 912) in men, before and after implementation of hs-cTn. Conclusions: In patients presenting with anginal symptoms, the diagnosis of acute myocardial infarction doubled after implementation of hs-cTn testing in both women and men. Use of sex-specific thresholds increased the proportion of patients with myocardial infarction who were women compared to use of a uniform threshold. Implementation was associated with a reduction in one-year mortality, but further research is needed to understand whether this is due to differences in the risk profile of patients with myocardial infarction or improvements in treatment. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This study was supported by a grant from Abbott Laboratories to S.J.R.M.